1992
DOI: 10.1021/bi00136a022
|View full text |Cite
|
Sign up to set email alerts
|

A vibrational analysis of the catalytically important C4-H bonds of NADH bound to lactate or malate dehydrogenase: ground-state effects

Abstract: We have measured the frequency of the carbon-hydrogen stretching mode of the pro-R and pro-S C4-H bonds of NADH in solution and when bound to pig heart lactate (LDH) or mitochondrial malate (mMDH) dehydrogenases. This is achieved by specifically deuterating the C4 pro-R or pro-S hydrogens of NADH and determining the frequencies of the resulting C4-D stretches by Raman difference spectroscopy. We find that the frequencies of the two C4-D stretching modes for the two bonds are essentially the same for the unliga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 26 publications
5
63
0
Order By: Relevance
“…Such a shift (or the absence of it) has been observed in various enzymes studied previously. 8,9,14,16,21 The band at 1547 cm 1 in the solutions spectrum of NADH [ Fig. 3(b)] is due to C C and C O stretch combinations based on vibrational calculations using ab initio quantum mechanical methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a shift (or the absence of it) has been observed in various enzymes studied previously. 8,9,14,16,21 The band at 1547 cm 1 in the solutions spectrum of NADH [ Fig. 3(b)] is due to C C and C O stretch combinations based on vibrational calculations using ab initio quantum mechanical methods.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, while large shifts from solution positions are observed for some bands of the C C stretch character and the carboxamide C O stretch and NH 2 rock, for NADH bound to LDH, none are found for NADH bound to G3PDH. It is most likely that the nicotinamide ring, which can adopt a range of angles from half-boat to planar in solution, 14 freezes to a near-planar ring geometry when bound to G3PDH. This structural conclusion is corroborated by the observation that the wavenumbers of the two C-4-H stretches (pro-R and pro-S C-4-H) are nearly the same for NADH bound to G3PDH (data not reported).…”
Section: Discussionmentioning
confidence: 99%
“…Significant binding isotope effects have also been measured in the reaction catalysed by human brain hexokinase (Lewis and Schramm, 2003), lactate dehydrogenase (LaReau et al, 1989;Gawlita et al, 1995a, b), phosphoenolpyruvate carboxylase (Gawlita et al, 1995a, b), and pyruvate kinase (Gawlita et al, 1995a, b). Furthermore, a number of spectroscopic studies have demonstrated significant polarization of substrate carbonyls upon binding enzyme and prior to catalysis that would be expected to yield corresponding isotope effects on the binding steps (Belasco and Knowles, 1980;Kurz et al, 1985;Deng et al, 1989Deng et al, , 1992Tonge and Carey, 1992). Effects such as these also can be viewed as potential contributors to any measured kinetic isotope effect intended to evaluate the transition state during the step of actual covalent rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity ratios of these two bands are approximately 2:1 in both cases. In order to understand these spectral changes in terms of nicotinamide structural changes quantitatively, we have performed normal mode analysis based on quantum mechanical ab initio and semiempirical calculations (Deng, Burgner, & Callender, 1992; Deng, Zheng, Sloan, Burgner, & Callender, 1992). …”
Section: Active Site Structures By Vibrational Spectroscopy and Abmentioning
confidence: 99%
“…The orientation of the amide group affects the C4–D stretch frequency of the reduced nicotinamide ring. A rotation of the C=O bond from cisoid to transoid will raise both C4–D stretches by about 10–20 cm −1 (Deng, Zheng, Sloan, Burgner, & Callender, 1992). Hence, we expect that the average frequency of the two C4–D stretches will increase as NADH binds to LDH.…”
Section: Active Site Structures By Vibrational Spectroscopy and Abmentioning
confidence: 99%